Analysis of Clinical Efficiency and Safety of Laparoscopic Anus-Conserving Operation for Ultralow Rectal Cancer. Issue 5 (May 2019) - Zuo, Zhongkun; Ding, Ke; Tang, Tenglong; Zhang, Leiyi; Peng, Weihui; Deng, Yiren; Huang, Jiangsheng; Duan, Lunxi
To explore the efficiency and safety of laparoscopic anus-conserving operation for ultralow rectal cancer, we retrospectively reviewed 236 patients with ultralow rectal cancer who underwent laparoscopic anus-conserving operation (experimental group, n = 124) or conventional open surgery (control group, n = 112). Operation-related indexes, pathological results of mesentery, incidence rates of postoperative complications, anus preservation rates, anal sphincter controllability after surgery, and survival rates of the first, second, and third years after operation were compared between the two groups. The amount of intraoperative bleeding, first postoperative exhaust time, abdominal drainage, pain score, and hospital stay in the experimental group were significantly less than those in the control group ( P < 0.05). There were no significant differences in the postoperative circumferential resection margin, distal resection margin, number of dissected lymph nodes, successful resection rate, and quality of mesorectum between the two groups ( P > 0.05). The total incidence rate of postoperative complications, anal sphincter controllability, and survival rates after surgery were similar between the two groups ( P > 0.05). The anus preservation rate of the experimental group (84.7%) was significantly higher than that of the control group (69.6%) ( P < 0.05). Laparoscopic anus-conserving operation is effective and safe in treatment of patients with ultralow rectal cancer, which has advantages such as small trauma, less intra-operative bleeding, short hospital stay, rapid recovery, a low incidence rate of postoperative complications, and a high anus-preserving rate, so it is worthy of clinical application.